FGFR1 and FGFR2 in fibrolamellar carcinoma. Issue 5 (5th October 2015) - Graham, Rondell P; Garcia, Joaquin J; Greipp, Patricia T; Barr Fritcher, Emily G; Kipp, Benjamin R; Torbenson, Michael S
Abstract : Aims: Fibrolamellar carcinoma is characterized by a recurrent DNAJB1–PRKACA chimeric transcript. The functional properties of the fusion are unknown, but are believed to include PRKACA up‐regulation. PRKCA is a subunit of protein kinase A. The downstream targets of protein kinase A are unknown, but may include interactions with fibroblast growth factor receptor (FGFR) pathways. In addition, inhibitors for FGFR proteins have been developed recently. Methods and results: Nineteen histologically confirmed fibrolamellar carcinomas were studied. All showed the characteristic DNAJB1–PRKACA transcript by reverse transcription–polymerase chain reaction (RT–PCR). Immunohistochemistry for FGFR1 was negative in 19 of 19 cases using a monoclonal antibody, while a polyclonal antibody showed no expression ( n = 11) or weak and focal expression ( n = 8). RNA in‐situ hybridization was 2+ in two cases, 1+ in four cases and negative in four cases. FGFR1 fluorescence in‐situ hybridization (FISH) revealed polysomy of chromosome 8 in 17 of 19 cases. Break‐apart FISH for FGFR2 was negative for rearrangements in 12 of 12 informative cases. Conclusions: Fibrolamellar carcinomas show polysomy of chromosome 8 and the FGFR1 locus, and only modest mRNA expression and weak or absent expression at the protein level. FGFR2 rearrangement was not detected. These data reduce the likelihood that FGFR inhibitors will be effective in the treatment of most fibrolamellar carcinomas.